1991
DOI: 10.1002/1097-0142(19910101)67:1<91::aid-cncr2820670118>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic detection of the epidermal growth factor receptor in human esophageal squamous cell carcinoma

Abstract: Epidermal growth factor receptor (EGF-R) expression was studied immunohistologically in 38 patients with esophageal squamous cell carcinoma. The EGF-R was faintly expressed in basal and parabasal layers of normal esophageal epithelia and in cancer nests of 20 patients; it was strongly expressed in all areas of dysplastic epithelia and in cancer nests of 18 patients. The patients with strongly expressed EGF-R had lymph node metastases more frequently, and their prognosis was poorer than those with faintly expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1
3

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 17 publications
3
36
1
3
Order By: Relevance
“…As done for breast cancer, HER2 staining was evaluated in a semiquantitative way with a cutoff of 10% '3 þ ' cells (PenaultLlorca et al, 2002). Tumour cells were considered to be 'EGFR positive' when their staining was more marked than that of the adjacent normal epithelium, in agreement with previous interpretations of EGFR in SCCO (Yano et al, 1991;Itakura et al, 1994). Whenever they had been found positive, we evaluated the percentage of cells displaying the same intensity of staining.…”
Section: Staining Evaluationsupporting
confidence: 80%
See 1 more Smart Citation
“…As done for breast cancer, HER2 staining was evaluated in a semiquantitative way with a cutoff of 10% '3 þ ' cells (PenaultLlorca et al, 2002). Tumour cells were considered to be 'EGFR positive' when their staining was more marked than that of the adjacent normal epithelium, in agreement with previous interpretations of EGFR in SCCO (Yano et al, 1991;Itakura et al, 1994). Whenever they had been found positive, we evaluated the percentage of cells displaying the same intensity of staining.…”
Section: Staining Evaluationsupporting
confidence: 80%
“…According to literature data, EGFR overexpression in this pathology ranges from 45.6 to 72.1% (Itakura et al, 1994;Shimada et al, 1999); our results are consistent with these findings. Most of the studies found a significant relationship to metastasis occurrence (Shimada et al, 1999), lymph node involvement and survival (Yano et al, 1991). By using EGF-binding assays, Ozawa and Coll (1989) and Mukaida and Coll (1991) drew the same conclusions, and so did Kitagawa and Coll (1996) from slot-blot hybridation experiments.…”
Section: Epidermal Growth Factor Receptor In Sccomentioning
confidence: 89%
“…In particular, we and others have recently reported that the overexpression of EGFR of oesophageal SCC, partially accounted for by gene amplification, is found in 50 -70% (Itakura et al, 1994;Hanawa et al, 2006), and is indicative of a poor prognosis (Ozawa et al, 1989;Yano et al, 1991). Moreover, we showed that the overexpression of HER-2 in oesophageal SCC was found in 30.3% (Mimura et al, 2005b).…”
supporting
confidence: 66%
“…Patients who had tumors that expressed EGFR had shorter disease-free and overall survival compared with patients who had EGFR-negative tumors, but EGFR expression was not an independent prognostic indicator for either parameter in multivariate analysis. Although there have been several studies of EGFR expression in esophageal squamous cell carcinomas, 21,[25][26][27][35][36][37][38] studies of the role of EGFR in esophageal adenocarcinomas have been limited. 28,29,39 Similar to our studies, the majority of the esophageal adenocarcinomas in previous studies were from the lower one-third of the esophagus or from the GEJ.…”
Section: Discussionmentioning
confidence: 99%
“…10 Protein overexpression or gene amplification of EGFR has been reported in several human tumors of epithelial origin, including head and neck, [11][12][13] thyroid, 14 breast, 15,16 ovarian, 17 , colon, [18][19][20][21] cervix, bladder, 22 stomach, and lung 23 cancers. In a subset of these tumors, most notably breast cancer, 16,19,24 colorectal cancer, [18][19][20][21] and esophageal squamous cell carcinoma, 21,25,26 increased EGFR expression has been associated with advanced disease, development of metastases, and poor clinical prognosis. Whether EGFR plays a similar role in esophageal adenocarcinoma is not clear.…”
mentioning
confidence: 99%